Landscape diversity influences the arthropod species diversity in the rice field - Ali, M. P.; Biswas, M.; Clemente-Orta, Gemma; Kabir, M. M. M.; Datta, Juel; Haque, S. S.; Qin, Xinghu; Landis, Douglas; Kaur, Parwinder; Pittendrigh, Barry R.; Howlader, M. T. H. (Frontiers in Environmental Science, 2022)
Landscape diversity is one of the key drivers for maintaining ecosystem services in agricultural production by providing vital habitats and alternative food sources for beneficial insects and pollinators within the agricultural landscapes. The landscape structure, land uses, and diversity differ between geographic locations. However, how the changes of landscape structure and land use diversity affect the arthropod diversity in a geographic area is poorly understood. Here, we tested the impact of landscape diversity on the rice locations in Bangladesh. Results ranged from highly diversified to very highly diversified in Chattogram (>7.9), to highly diversified (0.590.79) in Satkhira and moderately (0.390.59) to less diversified (0.190.39) in Patuakhali. These significant different landscape diversities influenced the arthropod diversity in rice fields. Arthropod species diversity increases with the increase in the Land Use Mix (LUM) index. The maximum tillering stage of rice growth harbored higher abundance and species diversity in rice fields. Moreover, we found that vegetation is the most important factor influencing the abundance of arthropods. Extensive agriculture and forest contributed substantially to predicting arthropod richness. Meanwhile, barren land and high-density residential land as well as intensive agriculture had large impact on species diversity. This study indicates that landscape diversity plays a vital role in shaping the species diversity in rice fields, providing guidelines for the conservation of arthropod diversity, maximizing natural pest control ecosystem service and more secure crop production itself.